Tospovirus(es) infecting grain legumes in Delhi – their identification by serology and nucleic acid hybridization - NARESH CHANDRA and S.K. LAL, A.I. BHAT*, R.K. JAIN, A. VARMA (Indian Phytopathology, 2002)
A survey for the presence of tospovirus infections on blackgram, cowpea, greengram and soybean fields at Delhi during August to October 1999 was carried out. Veinal necrosis, tip necrosis, stem, petiole and pod necrosis, and chlorotic lesions were the common symptoms observed in affected plants. Isolates induced chlorotic and necrotic lesions, and systemic infection in cowpea (cv. Pusa Komal) upon mechanical inoculation. Of the seven different tospovirus antisera tested against these isolates in direct antigen - coated (DAC) - ELISA, positive reactions were seen only with groundnut bud necrosis virus (GBNV) and watermelon silver mottle virus (WSMV). In nucleic acid hybridization tests, isolates hybridized only with nucleo-capsid protein (NP) gene of GBNV and not with NP gene of tomato spotted wilt virus (TSWV). Non-reaction of soybean isolates with WSMV antiserum indicated antigenic variations among the isolates under study.